PENINGKATAN KEMAMPUAN MENYIMAK MELALUI METODE BERCERITA PADA ANAK USIA 5-6 TAHUN - Endang Endang; Purwanti Purwanti; Muhamad Ali (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this research. This research is to describe, 1) Learning plans toincrease listening skills through children's storytelling methods, 2)implementation of increasing listening skills through Children’sstorytellingmethods, 3)improve listening skills through children’s storytellingmethods.Researchers use descriptive methods. The result of this research isClassroom Action Research. The conclusion of this study is: 1) Planning forlearning to increase listening skills through children’s storytelling methods. is inaccordance with the predetermined stages with the category not implemented incycle 1 and in cycle II with the category carried out well,2) implementation ofincreasing listening skills with children's storytelling methods, has beenimplemented by the teacher well,because the teacher implements in accordancewith the planning made both cycle I and cycle, and, 3) increase in listening skillsthrough children's storytelling methods in cycle 1 value which is categorized asnot good whereas in cycle II it increased very well with a value of 81.82Keywords: Listening skills, storytelling method